Deregulation of Exo70 Facilitates Innate and Acquired Cisplatin Resistance in Epithelial Ovarian Cancer by Promoting Cisplatin Efflux - Zhao, Yujie (Cancers (Basel), 2021)
SIMPLE SUMMARY: Innate and acquired platinum resistance are the leading causes of epithelial ovarian cancer (EOC) mortality. However, the mechanisms remain elusive. Here we found that Exo70, a key subunit of the exocyst, is upregulated in EOC and promotes cisplatin efflux to facilitate innate resistance. More interestingly, cisplatin could downregulate Exo70 to sustain cell sensitivity. However, this function was hampered during prolonged cisplatin treatment, which in turn stabilized Exo70 to facilitate the acquired cisplatin resistance of EOC cells. Our study potentiates Exo70 as a promising target to overcome cisplatin resistance in EOC. ABSTRACT: Whilst researches elucidating a diversity of intracellular mechanisms, platinum-resistant epithelial ovarian cancer (EOC) remains a major challenge in the treatment of ovarian cancer. Here we report that Exo70, a key subunit of the exocyst complex, contributes to both innate and acquired cisplatin resistance of EOC. Upregulation of Exo70 is observed in EOC tissues and is related to platinum resistance and progression-free survival of EOC patients. Exo70 suppressed the cisplatin sensitivity of EOC cells through promoting exocytosis-mediated efflux of cisplatin. Moreover, cisplatin-induced autophagy-lysosomal degradation of Exo70 protein by modulating phosphorylation of AMPK and mTOR, thereby reducing the cellular resistance. However, the function was hampered during prolonged cisplatin treatment, which in turn stabilized Exo70 to facilitate the acquired cisplatin resistance of EOC cells. Knockdown of Exo70, or inhibiting exocytosis by Exo70 inhibitor Endosidin2, reversed the cisplatin resistance of EOC cells both in vitro and in vivo. Our results suggest that Exo70 overexpression and excessive stability contribute to innate and acquired cisplatin resistance through the increase in cisplatin efflux, and targeting Exo70 might be an approach to overcome cisplatin resistance in EOC treatment.